HLA tissue status in patients with gluten sensitive enteropathy - Ahmet TEZEL; Aysel ÜLKER; Arzu ENSARİ and Çağlar BAYSAL and Klara DALVA and Ülkü DAĞLI and Azmi SERİN and Hülya ÖVER and Canan ALKIM (Turkish Journal of Gastroenterology, 2019)
-